PATH-11. THE LONGITUDINAL EVOLUTIONARY TRAJECTORY OF OLIGODENDROGLIOMA IS DRIVEN BY TREATMENT-ASSOCIATED GENETIC ALTERATIONS. (14th November 2022) - Varn, Frederick; Ye, Gordon; Ghospurkar, Padmaja; Wade, Taylor; Khasraw, Mustafa; Lipp, Eric S; Hermes, Beth; Elliott, Carol; Costello, Joseph F; Hong, Chibo; French, Pim; Vallentgoed, Wies; et al.
Abstract: Oligodendroglioma is a subtype of diffuse glioma defined by a mutation in the isocitrate dehydrogenase (IDH) genes and a co-deletion of chromosome arms 1p and 19q. These tumors primarily occur in adult patients in their third and fourth decade of life and are universally fatal due to an inevitable recurrence that follows a treatment regimen of surgical resection and an optional combination of alkylating chemotherapy and/or radiation therapy. While initially slow growing, recurrent tumors exhibit increasingly aggressive phenotypes that become progressively more difficult to treat with conventional therapy. Currently, the molecular mechanisms and cellular phenotypes that drive this recurrence remain unknown. To understand these factors, we assembled a cohort of matched initial and recurrent oligodendroglioma samples from over 100 patients and performed whole-genome sequencing and whole-exome sequencing on each of them. To link these molecular profiles to cell state changes, we additionally performed bulk and single-nucleus RNA-sequencing on a subset of these tumor pairs. In nearly 40% of alkylating chemotherapy-treated patients, recurrent tumors presented with hypermutation that corresponded with an increase in neoplastic cell proliferation. Additionally, while individual somatic alterations specific to recurrence were relatively rare, we observed a subset of tumors that acquired deletions in the cell cycle regulator CDKN2A following treatment with radiotherapy. Acquisition of either of these features associated with shorter patient survival and higher grade at recurrence, implicating cell cycle dysregulation as a mechanism of treatment resistance and increased tumor severity. Together, these results indicate that oligodendrogliomas evolve in a treatment-specific manner following chemo- and radiation therapy and highlight key pathways that can be targeted to delay the onset of recurrence.